2014
DOI: 10.1080/09692290.2014.955518
|View full text |Cite
|
Sign up to set email alerts
|

The peripheralization of Southern European capitalism within the EMU

Abstract: The paper discusses the problem of the Southern European (SE) capitalism and its difficult path into the EMU (European Monetary Union), looking at the remote causes of the crisis that hit these economies. For this reason, we consider European countries as a set of asymmetrically integrated variety of capitalism. The institutional configuration chosen by Europe to aggregate the many varieties of capitalism not only reduced the political autonomy of the single states, but effectively hindered the specific coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 26 publications
0
36
0
1
Order By: Relevance
“…On the other side, some CCC scholars find their prime source of inspiration not in ( post-)VoC, but in the (institutionalist) Regulation perspective, Dependency theory and post-Kaleckian macroeconomics. Still they come to similar conclusions about the fragile interdependence between nationally distinct capitalisms within the EMU (Stockhammer, 2011(Stockhammer, , 2013Armingeon and Baccaro, 2012;Becker and Jäger, 2013;Regan, 2013Regan, , 2015Becker, 2014b;Gambarotto and Solari, 2015;Jessop, 2014;Stockhammer et al, 2014;Baccaro and Benassi, 2015;Baccaro and Pontusson, 2015;Johnston and Regan, 2015;Suau Arinci et al, 2015). Here, however, the focus is not only on supply-side institutions (and companies), but also on demand-side institutions such as collective bargaining and unemployment insurance (and household indebtedness), and these scholars often do not speak of CMEs, but of export-led or profit-led growth regimes (or models), in contrast to the demand-/ consumption-/debt-/wage-led growth regimes that typically can be found in LMEs and MMEs.…”
Section: Three Generations Of CC Researchmentioning
confidence: 87%
See 3 more Smart Citations
“…On the other side, some CCC scholars find their prime source of inspiration not in ( post-)VoC, but in the (institutionalist) Regulation perspective, Dependency theory and post-Kaleckian macroeconomics. Still they come to similar conclusions about the fragile interdependence between nationally distinct capitalisms within the EMU (Stockhammer, 2011(Stockhammer, , 2013Armingeon and Baccaro, 2012;Becker and Jäger, 2013;Regan, 2013Regan, , 2015Becker, 2014b;Gambarotto and Solari, 2015;Jessop, 2014;Stockhammer et al, 2014;Baccaro and Benassi, 2015;Baccaro and Pontusson, 2015;Johnston and Regan, 2015;Suau Arinci et al, 2015). Here, however, the focus is not only on supply-side institutions (and companies), but also on demand-side institutions such as collective bargaining and unemployment insurance (and household indebtedness), and these scholars often do not speak of CMEs, but of export-led or profit-led growth regimes (or models), in contrast to the demand-/ consumption-/debt-/wage-led growth regimes that typically can be found in LMEs and MMEs.…”
Section: Three Generations Of CC Researchmentioning
confidence: 87%
“…By taking this into account, the implications for overcoming the crisis in the European South are not getting better, since the thorough de-industrialization that went hand-in-hand with financialization in Southern Europe will inhibit any quick recovery, unless compensated by a new credit-based boom. In fact, Southern European capitalisms have been even more 'peripheralized' than before (Gambarotto and Solari, 2015). Germany, in turn, suffers from a highly problematic specialization in manufacturing exports that may not be stable in the years to come, particularly due to rising inequality, limited exports to Southern Europe as well as increasing competition from emerging markets moving up in the manufacturing value chain (Baccaro and Benassi, 2015;Baccaro and Pontusson, 2015;Bruff, 2015).…”
Section: Growth Regimes: Private Sector Debt and Household Financialimentioning
confidence: 99%
See 2 more Smart Citations
“…The periphery, however, is not a stable entity – especially in Europe. In the aftermath of the global financial crisis, various authors (notably Gambarotto & Solari ; see also Vliegenthart ) observed that peripheralization dynamics common in post‐transition Eastern Europe are increasingly common in countries like Portugal, Italy, Ireland, Greece, and Spain (PIIGS). Despite this convergence, the PIIGS maintain an economic and political edge over their Eastern European neighbours (Belojevikj & Mattioli ).…”
Section: Peripheral Financialization and The Macedonian Pathmentioning
confidence: 99%